[AR] Dawr Wasa'il al-Tawasul al-Ijtima'i al-'Arabiyyah wa al-Malayuwiyyah fi al-Hadd min Tafashshi al-Lahn wa Isna' al-Kifayah al-Lughawiyyah The Role of Arabic and Malay Social Media in Curbing the Spread of Linguistic Errors and Promoting Linguistic Competence - Youssef, Mohamed Abdelrahman Ibrahim (Penerbit UniSZA, Universiti Sultan Zainal Abidin (UniSZA), 2025)
This study deals with the role played by social media in reducing the spread of common linguistic errors and improving linguistic competence among students, as well as those interested in the Arabic language and keen to learn it. The researcher adopted the analytical inductive approach, and the study yielded several results, including: There are many terms that indicate a departure from the linguistic norm among Arabs, including: incorrect pronunciation, mistake, and error, and there is no dispute over the term; old and contemporary sources used all of these terms, and social media also plays an important role in serving the Arabic language and reducing - to some extent – these linguistic errors. This is done in a direct way represented by linguistic corrections, and an indirect way manifested in linguistic refinement by enhancing the linguistic skills through the content related to Arabic syntax, morphology linguistic differences.